If I had the chance : artwork from the streets of Asia and the Pacific (Manila, Philippines : Asian Development Bank, 2003)
This collection features the artwork and words of impoverished child artists living on the streets of Bangladesh, Cambodia, Indonesia, Mongolia, Nepal, Papua New Guinea, and the Philippines. The children, who live on the margins of some of the poorest societies in the world, have produced poignant and expressive pieces of work, demonstrating how little is needed to nurture artistic talent. Proceeds from the sale of this book will be shared among the NGOs that played lead roles in the second Asian Development Bank Street Children's Art Competition and will be used for the direct benefit of the children under their care.
Keywords: CHILDREN'S ART -- COMPETITIONS -- ASIA